Single-Cell Transcriptional Analysis Deciphers the Inflammatory Response of Skin-Resident Stromal Cells - Liu, Baoyi; Li, Ang; Xu, Jingkai; Cui, Yong (Frontiers in Surgery, 2022)
The skin is the outermost barrier of the body. It has developed a sophisticated system against the ever-changing environment. The application of single-cell technology has revolutionized dermatology research, and unraveled the changes and interactions across skin resident cells in healthy and inflamed skin. Single-cell technology has revealed the critical roles of stromal cells in inflammatory response and explained a series of plausible past findings concerning skin immunity. Here, we summarized the functional diversity of skin stromal cells defined by single-cell analysis and how they orchestrated events leading to inflammatory diseases, including atopic dermatitis, psoriasis, vitiligo, and systemic lupus erythematosus.